Additive Antiproliferative and Antiangiogenic Effects of Metformin and Pemetrexed in a Non-Small-Cell Lung Cancer Xenograft Model - Wang, Jiun-Long; Lan, Ying-Wei; Tsai, Yi-Ting; Chen, Ying-Cheng; Staniczek, Theresa; Tsou, Yung-An; Yen, Chih-Ching; Chen, Chuan-Mu (Frontiers in Cell and Developmental Biology, 2021)
Lung cancer is heterogeneous and challenging to cope with once it has progressed. Chemotherapy is the first step once no active driver mutation has been discovered. Non-antitumor drugs have been found to be beneficial when used as adjuvants to chemotherapy. In this study, the additive effect and mechanism of metformin combined with pemetrexed in non-small-cell lung cancer (NSCLC) cells were elucidated. Three NSCLC cell lines, A549, H1975, and HCC827, were used to analyze tumor cell proliferation, colony formation and the cell cycle in vitro when exposed to metformin alone, pemetrexed alone or their combination. We found that combination treatment in three cell lines exerted antiproliferative effects through cell cycle arrest in the S phase. An ex vivo chicken chorioallantoic membrane (CAM) assay was used to examine the antiangiogenic effect of metformin combined with pemetrexed on vascular structure formation. We further created an A549 orthotopic xenograft model with an in vivo imaging system (IVIS) and explored the associated indicators involved in the tumorigenic process. The in vitro results showed that the combination of metformin and pemetrexed exhibited an antiproliferative effect in reducing cell viability and colony formation, the downregulation of cyclin D1 and A2 and the upregulation of CDKN1B, which are involved in the G1/S phase. For antiangiogenic effects, the combination therapy inhibited the vascular structure, as proven by the CAM assay. We elucidated that combination therapy could target VEGFA and Endoglin by RT-qPCR, ELISA and histopathological findings in an A549 orthotopic NSCLC xenograft model. Our research demonstrated the additive antiproliferative and antiangiogenic effects of the combination of metformin with pemetrexed in NSCLC and could be applied to clinical lung cancer therapy.